2011
DOI: 10.4103/1596-3519.82080
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided percutaneous fine needle aspiration biopsy / automated needle core biopsy of abdominal lesions: Effect on management and cost effectiveness

Abstract: Aims: This prospective study was designed to determine whether ultrasound (US)-guided percutaneous fi ne needle aspiration biopsy (PFNAB)/US-guided percutaneous needle core biopsy (PNCB) of abdominal lesions is effi cacious in diagnosis, is helpful in treatment choice, to evaluate whether various other investigations can be avoided, especially invasive ones, its time (shortening hospitalization) and cost-effectiveness. Materials and Methods: A total 159 US-guided PFNAB (67) and US-guided automated PNCB (92) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Genetic testing was employed for treatment selection in patients ( N = 7) [ 40 46 ] or to test for a familial disease in patients and their relatives ( N = 6) [ 47 52 ]. Biomarkers were applied to diagnose several types of cancer ( N = 23) [ 20 , 21 , 24 30 , 32 40 , 44 48 ], cardiovascular/circulatory diseases ( N = 9) [ 22 , 23 , 31 , 41 , 43 , 49 52 ], and respiratory disease ( N = 1) [ 42 ]. Economic evaluations were most often performed in colorectal cancer and evaluated genetic testing strategies like testing of BRAF and KRAS genetic mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic testing was employed for treatment selection in patients ( N = 7) [ 40 46 ] or to test for a familial disease in patients and their relatives ( N = 6) [ 47 52 ]. Biomarkers were applied to diagnose several types of cancer ( N = 23) [ 20 , 21 , 24 30 , 32 40 , 44 48 ], cardiovascular/circulatory diseases ( N = 9) [ 22 , 23 , 31 , 41 , 43 , 49 52 ], and respiratory disease ( N = 1) [ 42 ]. Economic evaluations were most often performed in colorectal cancer and evaluated genetic testing strategies like testing of BRAF and KRAS genetic mutations.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Gani et al ( 2011 ) of 67 cases concluded that the FNA procedure played a significant role in obtaining a diagnosis in the majority of patients, with no major clinical complications observed. In the veterinary world, the success of obtaining a diagnosis using FNA for abdominal organs is variable.…”
Section: Risk Versus Benefit Of Fnamentioning
confidence: 99%
“…Numerous studies carried out in human medicine also confirmed that FNF is safety and represents the effectiveness of biopsy (Gazelle at al. 1992, Vignoli and Saunders 2009, Gani at al. 2011).…”
Section: Spleenmentioning
confidence: 99%
“…Prior to biopsy an ultrasound examination must be performed in order to precisely evaluate location of lesions, their size and depth of situation as well as to determine the best biopsy needle insertion site (Wang at al. 2004, Gani at al. 2011.…”
Section: Fine Needle Aspiration Biopsy Techniquementioning
confidence: 99%
See 1 more Smart Citation